The Ickabog [compact disc, unabridged] - Rowling, J. K. (Brilliance Audio, 2021)
The kingdom of Cornucopia was once the happiest in the world. It had plenty of gold, a king with the finest moustache one could possibly imagine, and butchers, bakers, and cheesemongers whose exquisite foods made a person dance with delight when they ate them. Everything was perfect, except for the misty Marshlands to the north, which, according to legend, were home to the monstrous Ickabog. Anyone sensible knew that the Ickabog was just a myth to scare children into behaving. But the funny thing about myths is that sometimes they take on a life of their own. Could a myth unseat a beloved king? Could a myth bring a once happy country to its knees? Could a myth thrust two children into an adventure they didn't ask for and never expected?